Basic College Mathematics (10th Edition)

Published by Pearson
ISBN 10:
ISBN 13:

Chapter 3 - Adding and Subtracting Fractions - 3.5 Order Relation and the Order of Operations - 3.5 Exercises - Page 245: 58



Work Step by Step

$\frac{6}{5} \div (\frac{3}{5} - \frac{3}{10})$ = $\frac{6}{5} \div (\frac{6}{10} - \frac{3}{10})$ = $\frac{6}{5} \div \frac{3}{10}$ = $\frac{6}{5} \times \frac{10}{3}$ = $\frac{60}{15}$ = 4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.